Geminated Maxillary Lateral Incisor with Two Root Canals - Nayara Romano; Luis Eduardo Souza-Flamini; Isabela Lima Mendonça; Ricardo Gariba Silva; Antonio Miranda Cruz-Filho (Hindawi Limited, 2016)
This paper reports a case of gemination in a maxillary lateral incisor with two root canals and crown-root dilaceration. A 16-year-old male patient was referred for endodontic treatment of the maxillary left lateral incisor and evaluation of esthetic and functional complaints in the anterior region. The patient reported trauma to the anterior primary teeth. There was no spontaneous pain, but the tooth responded positively to the vertical percussion test and negatively to the pulp vitality test. Clinical examination showed esthetic and functional alterations and normal periodontal tissues. CBCT imaging confirmed the suspicion of gemination and crown-root dilaceration and also revealed the presence of two root canals and periapical bone rarefaction. The root canals were instrumented with Reciproc R40 and 1% NaOCl irrigation and were filled by lateral condensation of gutta-percha and AH Plus sealer. The tooth was definitely restored with composite resin to recover esthetics. Continued follow-up over 6 months has shown absence of pain or clinical alterations as well as radiographic image suggestive of apical repair.